Pengaruh Faktor Financial dan Non-Financial Terhadap Financial Distress: Studi pada Industri FNB yang Terdaftar di BEI Periode 2016 – 2021 - Nadia Indah Oktaviani; Gatot Nazir Ahmad; Destria Kurnianti (Journal of Business Application, 2023)
The purpose of this study was to examine the effect of CEO education, CEO expertise, leverage, and operating cash flow on financial distress in the food and beverage industry listed on the IDX for the 2016 to 2021 period. This study used a quantitative method with purposive sampling as a sampling method. The samples obtained were 102 companies and the type of data used was secondary data consisting of financial reports from 2016 to 2021 and each company's CEO profile. The data analysis technique used is logistic regression analysis. Based on the results of this study, it is known that CEO education, CEO expertise,and leverage do not have a significant effect on financial distress, while operating cash flow has a significant effect in a negative direction on financial distress.